Prevalence and Molecular Characterization of Carbapenemase-Producing Multidrug-Resistant Bacteria in Diabetic Foot Ulcer Infections - Mohd Saleem; Soha Abdallah Moursi; Tahani Nasser Almofeed Altamimi; Mohammed Salem Alharbi; Alwaleed Mohammad Alaskar; Sahar Adly Hassan Hammam; Ehab Rakha; Ozair Ilyas Syed Muhammad; Hamoud Abdulmohsin Almalaq; Metab Nasser Alshammari; Azharuddin Sajid Syed Khaja (Diagnostics)
Background: Diabetic foot ulcers (DFUs) represent severe complications in diabetic patients, often leading to chronic infections and potentially resulting in nontraumatic lower-limb amputations. The increasing incidence of multidrug-resistant (MDR) bacteria in DFUs complicates treatment strategies and worsens patient prognosis. Among these pathogens, carbapenemase-producing pathogens have emerged as particularly concerning owing to their resistance to β-lactam antibiotics, including carbapenems. Methods: This study evaluated the prevalence of MDR bacteria, specifically carbapenemase-producing pathogens, in DFU infections. A total of 200 clinical isolates from DFU patients were analyzed via phenotypic assays, including the modified Hodge test (MHT) and the Carba NP test, alongside molecular techniques to detect carbapenemase-encoding genes (blaKPC, blaNDM, blaVIM, blaIMP, and blaOXA-48). Results: Among the isolates, 51.7% were confirmed to be carbapenemase producers. The key identified pathogens included Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii, and Escherichia coli. The most commonly detected carbapenemase genes were blaKPC (27.6%) and blaNDM (24.1%). Carbapenemase-producing isolates presented high resistance to β-lactam antibiotics, whereas non-carbapenemase-producing isolates presented resistance through mechanisms such as porin loss and efflux pumps. Conclusions: The findings of this study highlight the significant burden of MDR infections, particularly carbapenemase-producing organisms, in DFUs. MDR infections were strongly associated with critical clinical parameters, including pyrexia (p = 0.017), recent antibiotic use (p = 0.003), and the severity of infections. Notably, the need for minor amputations was much higher in MDR cases (p < 0.001), as was the need for major amputations (p < 0.001). MDR infections were also strongly associated with polymicrobial infections (p < 0.001). Furthermore, Wagner ulcer grade ≥II was more common in MDR cases (p = 0.002). These results emphasize the urgent need for enhanced microbiological surveillance and the development of tailored antimicrobial strategies to combat MDR pathogens effectively. Given the high prevalence of carbapenem resistance, there is an immediate need to explore novel therapeutic options to improve clinical outcomes for diabetic patients with DFUs.